Denervation does not alter the number of neuronal bungarotoxin binding sites on autonomic neurons in the frog cardiac ganglion - Sargent, PB (J Neurosci, 1991)
The binding of neuronal bungarotoxin (n-BuTX; also known as bungarotoxin 3.1, kappa-bungarotoxin, and toxin F) was analyzed in normal and denervated parasympathetic cardiac ganglia of the frog Rana pipiens, n-BuTX blocks both EPSPs and ACh potentials at 5-20 nM, as determined by intracellular recording techniques. Scatchard analysis on homogenates indicates that cardiac ganglia have two classes of binding sites for 125I-n-BuTX: a high-affinity site with an apparent dissociation constant (Kd,app) of 1.7 nM and a Bmax (number of binding sites) of 3.8 fmol/ganglion and a low-affinity site with a Kd,app of 12 microM and a Bmax of 14 pmol/ganglion. alpha-Bungarotoxin does not appear to interfere with the binding of 125I-n-BuTX to either site. The high-affinity binding site is likely to be the functional nicotinic ACh receptor (AChR), given the similarity between its affinity for 125I-n- BuTX and the concentration of n-BuTX required to block AChR function. Light microscopic autoradiographic analysis of 125I-n-BuTX binding to the ganglion cell surface reveals that toxin binding is concentrated at synaptic sites, which were identified using a synaptic vesicle-specific antibody. Scatchard analysis of autoradiographic data reveals that 125I- n-BuTX binding to the neuronal surface is saturable and has a Kd,app similar to that of the high-affinity binding site characterized in homogenates. Surface binding of 125I-n-BuTX is blocked by nicotine, carbachol, and d-tubocurarine (IC50 less than 20 microM), but not by atropine (IC50 greater than 10 mM). Denervation of the heart increases the ACh sensitivity of cardiac ganglion cells but has no effect upon the number of high-affinity binding sites for 125I-n-BuTX in tissue homogenates. Moreover, autoradiographic analysis indicates that denervation does not alter the number of 125I-n-BuTX binding sites on the ganglion cell surface. n-BuTX is as effective in reducing ganglion cell responses to ACh in denervated ganglia as it is in normally innervated ganglia. These results suggest that denervation alters neither the total number of nicotinic AChRs in the cardiac ganglion nor the number found on the surface of ganglion cells. These autonomic neurons thus respond differently to denervation than do skeletal myofibers. The increase in ACh sensitivity displayed by cardiac ganglion cells upon denervation cannot be explained by changes in AChR number.